Pengaruh Kepemimpinan Kepala Sekolah, Kompetensi Guru, Kompensasi Guru Terhadap Kinerja Guru SMK - Salman Al Farisi; Raihan Raihan; Raden Afwah Dimas Manaafi; Achmad Sauri; Luluk Dwi Ratnandari (Universitas Indraprasta PGRI, 2025)
This research is motivated by the existence of several educators who experienced a decline in performance based on the results of the Teacher Competency Test (UKG) targeted by the government with an average score of 55, but the average UKG score data in several areas is still lower than the National UKG average, such as the performance score of Raudhatul Athfal teachers in Cakung District, East Jakarta City is still at 44. This study aims to (1) analyze the influence of principal leadership partially on teacher performance at SMK Daarul Uluum, South Jakarta, (2) analyze the influence of teacher competence partially on teacher performance at SMK Daarul Uluum, South Jakarta, (3) analyze the influence of teacher compensation partially on teacher performance at SMK Daarul Uluum, South Jakarta, (4) analyze the simultaneous influence of principal leadership, teacher competence and teacher compensation on teacher performance at SMK Daarul Uluum, South Jakarta. The research method used is a quantitative approach with a survey method on all educators (26 people), with a saturated sample method. The results of the study showed that (1) the principal's leadership did not have a significant effect on teacher performance at SMK Daarul Uluum South Jakarta, with a significant variable value of 0.842 > from the significance level α 0.05, (2) teacher competence had a positive and significant effect on teacher performance at SMK Daarul Uluum South Jakarta.